Utilizing a Professionalism Mentor to Address Sexual Harassment in Academic Ophthalmology - Cabrera, Michelle T.; Christopher, Karen L.; Collins, Megan E.; Ing, Eliesa; Sun, Grace; Pettey, Jeff H.; Simon, Shira S.; Sridhar, Jayanth; Soohoo, Jeffrey R.; Simpson, Rachel G.; Ding, Leona; Pineles, Stacy L. (Journal of Academic Ophthalmology, 2021)
Objective This study assesses a new departmental role—a professionalism mentor—who receives sexual harassment reporting, liaisons with campus resources, and organizes educational sessions.Study Design Multicenter randomized controlled survey study.Methods Academic ophthalmology departments in the United States were randomized to a professionalism mentor group (n = 9) and a control group (n = 7). Among both pre- and postsurveys, 605 faculty and trainee responses were received and 546 were complete. The intervention group was assigned a professionalism mentor with educational session for a 6- to 10-month period. Sexual harassment and reporting rate change over time were compared between the two groups.Results Among 546 anonymous responses, 16% experienced workplace sexual harassment during the prior 10 months. Location in the South or Midwest was a risk factor (p < 0.001). Victims were mostly women (76%), including residents/fellows (46%) and academic attendings (49%); perpetrators included patients (35%) and academic attendings (35%). Departments with and without a professionalism mentor had stable harassment from pre- to postsurvey (p = 0.95 comparing change). The professionalism mentor group had an increase in reporting to an authority from pre- to postsurvey (7–23%), whereas the control group had a decrease (27–12%; p = 0.07 comparing change). Most faculty and trainees in the interventional arm of this study recommended instituting a professionalism mentor with educational session (66% presurvey and 68% postsurvey), compared with educational session alone (25% presurvey and 23% postsurvey), or neither (9% presurvey and 9% postsurvey). Residency program directors in the professionalism mentor group even more strongly supported instituting both a professionalism mentor and educational program (100% presurvey and 100% postsurvey) as opposed to educational program alone (0% presurvey and 0% postsurvey) or neither (0% presurvey and 0% postsurvey).Conclusion This study identified a high sexual harassment rate in academic ophthalmology departments over a brief period. The presence of a professionalism mentor was viewed favorably and may lead to increased reporting.
Keywords: sexual harassment; faculty; ophthalmology; graduate medical education; residency; academic medicine; professionalism mentor; education; Title IX; prevention